Analisis Penerapan Sistem Akuntansi Klaim Jaminan Kecelakaan Kerja Dan Jaminan Kematian Pada BPJS Ketenagakerjaan Cabang Juanda - Nadifah Ita Purnamasari; Endah Susilowati; Nanda Wahyu Indah Kirana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims of knowing the procedures for claims for employment injury security and death security applied by the Juanda Branch of BPJS Ketenagakerjaan in order to produce a proper and adequate claim payment accounting system. This type of research uses descriptive research with a qualitative approach. The data used in this study are primary data and secondary data. Primary data was obtained directly through interviews while secondary data was obtained through official documents related to claims for work accident insurance and death benefits. The results showed that the accounting system for work accident claims and death benefits applied to the Juanda Branch of Employment BPJS complies with PP No. 44 of 2015. However, overall the accounting system that is applied is not effective because the system is still experiencing problems caused by the participants' lack of knowledge regarding the requirements that must be attached in submitting claims and services that are only carried out directly at the office. A letter of heirs made by the relevant agency and a chronology of events made by the company or the police are documents that are often not attached by participants. Keywords: Accounting System, Employment Injury Security, Death Security